International relations - Goldstein, Joshua S., 1952-; Pevehouse, Jon C., 1973- (Boston : Longman, 2012)
A brief version of the bestselling comprehensive survey, International Relations presents the same approach and coverage but in a streamlined and flexible format. From war and trade to human rights and the environment, this text wins praise for being the most current introduction to international relations theory as well as security, economic, and global issues. Applying a broad range of theoretical perspectives to help students analyze what is happening in the world today, International Relations, Brief Edition is perfect for courses where multiple texts are assigned.
Includes bibliographical references and index.
"International edition"--Cover.
Keywords: Go international; International office; International relations; Internationale economie; Internationale politiek; Internationale relaties